2021
DOI: 10.14744/phd.2021.59480
|View full text |Cite
|
Sign up to set email alerts
|

Negatıve Emotıons Experıenced By Nursıng Students Durıng Clınıcal Practıce And Theır Copıng Experıences: A Focus Group Intervıew

Abstract: Amaç: Bu araştırmada, hemşirelik öğrencilerinin klinik eğitimleri sırasında yaşadıkları olumsuz duygular ile baş etme deneyimlerinin ortaya konması amaçlanmıştır. Gereç ve Yöntem: Aydın Adnan Menderes Üniversitesi 2018-2019 eğitim öğretim yılı, Hemşirelik Fakültesinde 2, 3 ve 4. sınıfta okuyan toplam 10 öğrenci araştırmanın çalışma grubunu oluşturmuştur. Çalışma grubu maksimum çeşitlilik örneklemesine göre belirlenmiştir. Araştırma, niteliksel, olgu bilim (fenomenolojik) desende yapılmıştır. Veriler, odak grup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Nursing students who are doing their first clinical training encounter additional hurdles owing to a lack of knowledge during the early clinical practicum. Prior qualitative studies, for example, indicated that nursing students were unsatisfied with their first clinical skills and found them stressful ( Alshowkan, 2022 ; Hwang et al, 2021 ; Öner & Karabudak, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nursing students who are doing their first clinical training encounter additional hurdles owing to a lack of knowledge during the early clinical practicum. Prior qualitative studies, for example, indicated that nursing students were unsatisfied with their first clinical skills and found them stressful ( Alshowkan, 2022 ; Hwang et al, 2021 ; Öner & Karabudak, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast, some students stated that they adapted to this process and were able to communicate easily. Relevant studies have revealed that the increased risk of contracting coronavirus increases the individuals' anxiety levels and affects them more in the social aspect (Arcadi et al, 2021;Gómez-Ibáñez et al, 2020;Öner and Sarıkaya Karabudak, 2021). Therefore, our study suggests that senior nursing students may be positively or negatively affected by the pandemic in the social aspect, as they spend most of their time in the clinic.…”
Section: Discussionmentioning
confidence: 60%
“…Students experience anxiety for reasons such as the risk of getting contracting coronavirus, becoming a contact or carrier, and interruption of their education due to the need to be quarantined in case of getting infected or becoming a contact (Yılmaz and Büyüköztürk, 2021;Türkleş et al, 2021;Gómez-Ibáñez et al, 2020;Seah et al, 2021). In the study by Öner and Sarıkaya Karabudak (2021), students were reported to experience positive emotions such as happiness, empathy, optimism, and conscience when they feel involved in clinical applications, see the outcomes of patient care, and receive positive feedback from patients. The findings of our study are parallel to the literature in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…This recommendation applies to students in the immigrant health center and those in other clinical units. Previous studies found that students’ feedback encouraged teaching staff to spend more time in program centers (Altundal et al, 2022; Öner & Karabudak, 2021).…”
Section: Discussionmentioning
confidence: 99%